2007
DOI: 10.1901/jaba.2007.737-741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individualized Video Feedback Combined With Group Parent Training on Inappropriate Maternal Behavior

Abstract: The effects of adding individualized video feedback (IVF) to Webster-Stratton's (2000, 2001) group-based parent training program (GT) were evaluated using a multiple baseline design across four mother-child dyads. During all phases of the study, inappropriate maternal behavior was recorded from videotapes of playtime with their preschoolers with developmental disabilities. Results suggested that GT+IVF reduced inappropriate maternal behavior to levels below GT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 10 publications
1
25
0
1
Order By: Relevance
“…Given that observations were relatively stable and significantly positively correlated, r = .96, p < .0001, I reduced the assessment to one observation per assessment point. This observation system (Phaneuf & McIntyre, 2007) uses partial-interval coding for seven parent inappropriate behavior categories (Inappropriate Play Behavior, Intrusion on Child’s Independence, Positive Consequences for Child’s Inappropriate Behaviors, Inappropriate Commands, Lack of Follow Through, Criticism, and Aggression) and event coding for Child-Directed Praise. All observations were videotaped and collected in the family home.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that observations were relatively stable and significantly positively correlated, r = .96, p < .0001, I reduced the assessment to one observation per assessment point. This observation system (Phaneuf & McIntyre, 2007) uses partial-interval coding for seven parent inappropriate behavior categories (Inappropriate Play Behavior, Intrusion on Child’s Independence, Positive Consequences for Child’s Inappropriate Behaviors, Inappropriate Commands, Lack of Follow Through, Criticism, and Aggression) and event coding for Child-Directed Praise. All observations were videotaped and collected in the family home.…”
Section: Methodsmentioning
confidence: 99%
“…All observations were videotaped and collected in the family home. A standardized set of materials and instructions were provided to parent–child dyads, which included 10-min free play, 2-min clean-up, and 3-min structured activity (e.g., puzzle) (Phaneuf & McIntyre, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Beyond providing families with skills videos as examples, technology also has the capacity to provide therapists a window on the parents’ use of the skills with the child outside of session. For example, HNC (Jones et al, 2014) and IY (Phaneuf & McIntyre, 2007) have both explored the utility of having parents video record their skill practice at home. In turn, therapists have an opportunity to review parent’s use of skills in context in order provide more tailored feedback, coaching, and support and to adjust session content and focus accordingly.…”
Section: Extensions Of Hanf-model Programs To Other Problems and Delimentioning
confidence: 99%
“…For example, Phaneuf and McIntyre (2007) tested the effect of adding individualized video feedback to a group-based IYS program (Webster-Stratton & Reid, 2010) for mothers of children with developmental disabilities, whom the authors highlight are at increased risk for disruptive behaviors. Findings from the multiple baseline design revealed that videotaping mother-child dyads, watching the videos with mothers, and providing feedback regarding inappropriate maternal behavior was more effective than the intervention without videotaped feedback.…”
Section: Technology In Bpt: Theory and Examplesmentioning
confidence: 99%